A Survey on the SETS-Based Human Anatomy and Physiology Course: Analysis of Instruments for Assessing Critical Thinking Skills Using Multimedia - Nuril Hidayati; Fariha Irmawati (Universitas Sebelas Maret, 2020)
Learning media must be followed the curriculum, accommodate learning activities, and provide an appropriate evaluation. The research objective was to determine the validity and reliability of the instrument for assessing the effectiveness of multimedia to promote critical thinking skills. A research method is a quantitative approach with a survey design. The study was conducted on 26 Biology Education students of IKIP Budi Utomosamples that were taken at least 20% of the population, 26 participants were taken more than 20% of a total of 82 students. The research instrument was a validation sheet for critical thinking skills assessment and 15 multiple choicesto test the understanding of the cardiovascular system. The validity and reliability data were analyzed using Anates Software. The results showed that the validity of the test instrument met the feasible criteria. The reliability value of the test instrument is 0.65 with a standard deviation of 2.84 which meets the high-reliability criteria. The distinctive power of the test instrument consisted of 20% poor, 26% criteriasufficient, and 53,33% very good. The level of difficulty of the test was 1 question categorized asvery difficult, 7 difficult, 5 moderate, and 2 questions werevery easy. Based on these results, the test instrument to measure students' critical thinking skills can be used as a reliable measuring tool in SETS-based multimedia in the human anatomy course